Replication Data for: Information exchange links, knowledge exposure, and adoption of agricultural technologies in northern Uganda - Shikuku, Kelvin Mashisia (International Center for Tropical Agriculture, 2019)
Replication dataset for the publication, “Information exchange links, knowledge exposure, and adoption of agricultural technologies in northern Uganda” (2017-05-01)